FbG as an around the clock support for an essay writing course amidst the pandemic - Tono Suwartono (EduLite: Journal of English Education, Literature and Culture, 2021)
This study aimed to explore the potential of Facebook Group (FbG) for teaching essay writing skills in the period of social distancing due to covid-19 pandemic. The study involved three groups of students who had been attending Essay Writing Course. Data was collected through questionnaires, interview, home assignments, and documents. Questionnaires were distributed via Google Form. Interviews were conducted with students through WhatsApp chats and calls. Descriptive statistics were used to analyse data obtained from closed questionnaires, home assignments, and mid-term test. Data from open questionnaires, interviews, and documents was analysed using qualitative inductive approach to identifying themes – topics, ideas, and patters of meaning. Study findings indicated that FbG has been an appropriate place for developing essay writing skills amidst the pandemic. FbG as networking site has made possible an effective, efficient, and practical essay writing learning for the following reasons.  Firstly, FbG discussion forum provided invaluable learning input. Secondly, FbG was easy to operate. The students could learn independently at their own pace.  Lastly, use of FbG brought them convenience and raised confidence to better engage in learning online. FbG has supported students’ essay writing learning process that has led to good writing performance. This can be seen not only from the conducive learning process in comparison to traditional classroom instruction prior to the pandemic, but also from learning outcome apparently observed in writing portfolios as well as mid-term test.